(untitled) (Lutas Sociais, 2022)
Lutas Sociais, v.26 n.48, jan./jun.2022. Dossiê América Latina Editor: Lúcio Flávio de Almeida (PUC, São Paulo-SP) Comitê editorial: Claudete Pagotto (UMESP, São Bernardo-SP), Eliel Machado (UEL, Londrina-PR), Jair Pinheiro (UNESP, Marília-SP), Lúcio Flávio de Almeida (PUC, São Paulo-SP).